Integrated bio-economic land use models: an analysis of the possibilities of sustainable natural forest management in the Atlantic Zone of Costa Rica - Marciano, C. (Research Program on Sustainability in Agriculture-REPOSA, Guápiles (Costa Rica) CATIE, Turrialba (Costa Rica) Wageningen Agricultural University, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
Fig. Tab. Bib. p. 90-97. Sum. (En). También como serie: Field Report (REPOSA) no. 182. Continuación de Field Report - Atlantic Zone Programme